Keterampilan Pendidik Abad 21 dalam Mengaplikasikan Pendekatan Student Centered Learning pada Mata Pelajaran Pendidikan Agama Islam - Moh. Faizin; Rifani Nabilla Rahman; Saniyyah Labibah; Vanissa Arum Saharani; Azmi Niswah Nabila (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2023)
Education today emphasizes the development of 21st-century skills, including critical thinking, creativity, collaboration, and communication. The Student Centered Learning approach is considered effective in facilitating the development of these skills by replacing the dominant role of the educator with a more facilitator-oriented role. This literature review aims to explain and analyze the 21st-century skills of educators in applying the Student Centered Learning approach to the subject of Islamic Religious Education. The results of the analysis indicate that the 21st-century skills of educators in applying the Student Centered Learning approach to Islamic Religious Education involve important aspects such as changes in the educator's role, the implementation of active learning strategies, the development of an inclusive learning environment, and the utilization of technology in Islamic religious education. Additionally, the research highlights the importance of adequate support and training for educators in developing these skills. This study provides a profound understanding of how 21st-century skills and the Student Centered Learning approach can be effectively applied in the subject of Islamic Religious Education. It can serve as a guide for Islamic Religious Education educators in designing relevant teaching strategies that meet the demands of the times and prepare students to face future challenges.